Portable sensory maze for autism / Shahidatul Hanisah Hamidi…[et al.] - Hamidi, Shahidatul Hanisah; Johari, Nurul Asyikin; Aznam, Ezzah Aliyah; Mohd Noor, Yani Arina; Wahab, Rosilah (Division of Research and Industry Linkages, 2017)
The ideas to make this innovation development of portable sensory maze for autism derived from combination game "Snakes and Ladders" and "Sensory Stimulation Kit". This project focusing on SENSORY to identify a field of a study upon individuals primarily children who demonstrated a typical behavioural responses to sensory stimulation. Children with autism or Pervasive Developmental Disorder (PDD) often have difficulty regulating sensory input from the environment. The sensory related problems include increased sensitivity to certain sounds, smells, tastes and touch. Other sensory problem also involves in proprioceptive and vestibular/ balance. Sensory Integration is the process by which people register, modulate, and discriminate sensations received through the sensory systems to produce purposeful, adaptive behaviours in response to the environment deliver consistent quality products. The games are created by combining these two sources "Sensory Maze" where use the concept of playing and rolling the dice to make a move with additional sensory to step on through the journey before completing the game with different textures that can be used from soft to rough surfaces. Thus, it contains 3 levels of games that the player must be completed which is gross motor activity in level 1, simple body awareness level 2 and combination of level 1 and 2 that have complex instruction with cognitive activities. By playing the sensory maze, clients will improve eye-hand coordination in order to improve handwriting capability, better in critical thinking to enhance problem solving, improve attention and concentration, promote crossing mid line to enhance cognitive integration and is useful to promote sensory discrimination for ADL functioning such as eating, wearing clothes and bathing.